RESPONS PEMBERIAN KOMPOS ECENG GONDOK PADA SEDIMEN DAERAH ALIRAN SUNGAI TONDANO TERHADAP PERTUMBUHAN JAGUNG - Steven C.N. Numberi; Meldi T.M. Sinolungan; Wiesje J.N. Kumolontang (Universitas Sam Ratulangi, 2017)
Tondano River is the outlet of Lake Tondano hold the important role for the community in the province of North Sulawesi. With the population growth, increasing the need of society to the river, so there are many problems, such as sedimentation. Sedimentation processes occur accompanied with the rise in erosion so there is more erosion discharge waste in the form of sediment contained in estuaries Tondano. The problem now is how the sediment which was originally a waste can be harnessed into something useful, which is used as a planting medium. This study aims to look at the response of composting hyacinth sediment Tondano Watershed indicators corn crop. Randomized Block Design, where as a control S0, S1 compost treated with 10 tons / ha, S2 compost treatment with 20 tons / ha, S3 compost treated with 30 tons / ha. This research was conducted in three groups in order to obtain 12 pot experiment. The observed variables plant height every week, every week the number of leaves, dry weight of plants after harvest. The results showed that giving the water hyacinth compost on Tondano River Sediments influenced on corn growth. The provision of water hyacinth compost with different doses affected the plant height, the number of leaves and dry weight. Â Keywords: sediment, water hyacinth, compost